Highly Stereoselective aza‐Baylis–Hillman Reactions of CF3‐Sulfinylimines: Straightforward Access to α‐Methylene β‐CF3 β‐Amino Acids. Issue 15 (23rd April 2014) - Milcent, Thierry; Hao, Jing; Kawada, Kosuke; Soloshonok, Vadim A.; Ongeri, Sandrine; Crousse, Benoit
Abstract: 1, 4‐Diazabicyclo[2.2.2]octane‐catalyzed asymmetric aza‐Baylis–Hillman (ABH) reaction of ( R )‐ N ‐ tert ‐butanesulfinyl‐(3, 3, 3)‐trifluoroacetaldimine with various Michael acceptors proceeds with exceptionally high rates and stereochemical outcome. This ABH approach provides convenient and practical access to previously unknown enantiomerically pure α‐methylene β‐CF3 β‐amino esters/acids, forthright useable for peptide synthesis. Abstract : 1, 4‐Diazabicyclo[2.2.2]octane (DABCO)‐catalyzed asymmetric aza‐Baylis–Hillman (ABH) reaction of ( R )‐ N ‐ tert ‐butanesulfinyl (3, 3, 3)‐trifluoroacetaldimine with various Michael acceptors proceeds with exceptionally high rates and stereochemical outcome. This ABH approach provides convenient and practical access to original, enantiomerically pure α‐methylene β‐CF3 β‐amino esters.